Changes in knowledge and beliefs of community health workers following an oral health intervention training program. Issue 1 (2nd January 2019) - Lumsden, Christie; Andrews, Howard; Leu, Cheng-Shiun; Edelstein, Burton
Abstract: Greater acknowledgement of the ways in which social determinants influence health has led to increased engagement of Community Health Workers (CHWs) in health promotion activities. This study sought to evaluate changes in CHW knowledge and beliefs via pre-/post-training surveys immediately following a four-day (∼20 hour) oral health intervention training and to gather CHW feedback on training. Significant increases in summary scores for 19 knowledge ( t (9) = −6.715, p < .001) and four belief ( t (9) = −2.994, p = .015) measures, using four-point Likert scales, were observed post-training. Feedback was overwhelmingly positive, with the majority of CHWs reporting confidence in understanding the material and study purpose. Findings support the effectiveness and acceptability of a brief training program to prepare CHWs to deliver an oral health intervention. CHWs hold promise to effectively engage populations in which the impact of interventions delivered by traditional oral healthcare team members has shown limited success.